TECHNICAL AND ECONOMIC PERFORMANCE OF WOMEN FISH PROCESSORS IN SOUTHERN BENIN FISH BASIN - ZANNOU, Afio; BABADANKPODJI, ADJOUA PASCALINE IDA; AOUDJI, KOSSI NOUNAGNON AUGUSTIN; Sognigbé, Gildas; Houngbo, SBE; SALIOU, Idelphonse; AHO, EDOUARD; Houessou, Donald; THOTO, Fréjus (My University, 2020)
Processing by hot smoking is a technique commonly used by women in the lagoon areas of Benin to preserve fish. The objective of this research was to assess the technical and economic efficiency of women fish processors in order to identify options for improving their income. Guided by the approach of stochastic production and cost frontiers, the results showed that the least technically efficient processor could reduce the amount of resources she used by 42.3 % in maintaining the same level of production. Also, the least economically efficient processor could save 73.7 % of its processing cost while maintaining the same level of production. Economically efficient processors spent less on variable inputs and financial services and sold smoked fish at a competitive price. The economic efficiency indices were significantly and positively correlated with net income. A processor could improve her net income by at least 23% by moving from her economic efficiency class to a higher class. The processors’ efficiency levels were determined by their status in the household, their experience and the type of ovens used. It is recommended that more efficient processors share smoked fish production practices with fewer resources to less efficient processors.
Keywords: Fish processing; efficiency; profitability; fishery; food security